Purification and characterization of a human factor that assembles and remodels chromatin. - LeRoy, G.; Loyola, A.; Lane, W.S.; Reinberg, D. (Journal of Biological Chemistry, 2000)
We have previously reported the isolation and characterization of a nucleosome remodeling and spacing factor, RSF. One of the RSF subunits is hSNF2h, a SNF2 homologue. Here we set out to isolate and characterize other hSNF2h-containing complexes. We have identified a novel hSNF2h complex that facilitates ATP-dependent chromatin assembly with the histone chaperone NAP-1. The complex possesses ATPase activity that is DNA-dependent and nucleosome-stimulated. This complex is capable of facilitating ATP-dependent nucleosome remodeling and transcription initiation from chromatin templates. In addition to hSNF2h, this complex also contains a 190-kDa protein encoded by the BAZ1A gene. Since both subunits are homologues of the Drosophila ACF complex (ATP-utilizing chromatin assembly and remodeling factor), we have named this factor human ACF or hACF.